2019
DOI: 10.3390/ijms20040937
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Specific Intron Retention Serves as Molecular Signature that Distinguishes Melanoma from Non-Melanoma Cancer Cells in Greek Patients

Abstract: Background: Skin cancer represents the most common human malignancy, and it includes BCC, SCC, and melanoma. Since melanoma is one of the most aggressive types of cancer, we have herein attempted to develop a gene-specific intron retention signature that can distinguish BCC and SCC from melanoma biopsy tumors. Methods: Intron retention events were examined through RT-sqPCR protocols, using total RNA preparations derived from BCC, SCC, and melanoma Greek biopsy specimens. Intron-hosted miRNA species and their t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 152 publications
(189 reference statements)
0
5
0
Order By: Relevance
“…Aberrant IR has previously been associated with disease phenotypes and clinical outcomes. For example, IR in CMYC and SESTRIN1 genes was shown to be a reliable molecular marker separating melanoma from non-melanoma tumours [ 14 ] and Sznajder and colleagues have shown that IR can be used as a biomarker in hereditary repeat expansion diseases [ 15 ]. Despite marked differences between tumour and normal breast tissue, IR profiles in our analysis also differ between ER + versus ER − tumours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant IR has previously been associated with disease phenotypes and clinical outcomes. For example, IR in CMYC and SESTRIN1 genes was shown to be a reliable molecular marker separating melanoma from non-melanoma tumours [ 14 ] and Sznajder and colleagues have shown that IR can be used as a biomarker in hereditary repeat expansion diseases [ 15 ]. Despite marked differences between tumour and normal breast tissue, IR profiles in our analysis also differ between ER + versus ER − tumours.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of IR in cancer has been emphasized following landmark discoveries about (i) aberrant IR patterns in leukaemia [ 10 , 11 ], (ii) IR as a source of neoepitopes [ 12 ], (iii) tumour suppressor gene inactivation by intronic polyadenylation [ 13 ], (iv) IR-based biomarkers [ 14 , 15 ], and (v) IR as a therapeutic target [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant IR has previously been associated with disease phenotypes and clinical outcomes. For example, IR in CMYC and SESTRIN1 genes was shown to be a reliable molecular marker separating melanoma from non-melanoma tumours 14 and Sznajder and colleagues have shown that IR can be used as biomarker in hereditary repeat expansion diseases 15 . Despite marked differences between tumour and normal breast tissue, IR profiles in our analysis also differ between ER + vs ER − tumours.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of IR in cancer has been emphasised following landmark discoveries about (i) aberrant IR patterns in leukemia 10,11 , (ii) IR as a source of neoepitopes 12 , (iii) tumour suppressor gene inactivation by intronic polyadenylation 13 , (iv) IR-based biomarkers 14,15 , and (v) IR as a therapeutic target 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Complex bioinformatics was performed, and the c-MYC, SRPX2, and Sestrin-1 genes were demonstrated to undergo intron retention just in melanoma. miRNAs were generated for these genes, and thus this pattern could molecularly differentiate other skin cancers from melanoma (Giannopoulou et al, 2019).…”
Section: Discriminating Melanoma From Other Skin Cancers Through Mirnasmentioning
confidence: 99%